Development of the Industrial Complex of Kryvoryzhya: Economic Benefits, Technogenic Consequences and Environmental Problems (London Journal of Research In Science: Natural and Formal, 2024)
The beginning of iron ore mining on an industrial scale in Kryvyi Rih almost 150 years ago became the impetus for the rapid industrial development of the region. As a result, only during the period from the 30s to the 90s of the 20th century, Kryvyi Rih turned from a small town into an industrial giant. The Kryvyi Rih region experienced rapid economic development, but at the same time, the industrial complex fundamentally changed the landscape and led to extremely serious environmental problems and man-made hazards. Therefore, it is important to study and research the geospatial changes of the territory, environmental hazards and search for solutions to the problems.The purpose of this study is to comprehensively highlight the positive economic factors of the development of the industrial complex of Kryvyi Rih and to study the geospatial changes of the territory as a consequence of the development of the mining and industrial complex.The task of the research is to highlight man-made and ecological problems and the environmental impact of the industrial complex in the city of Kryvyi Rih, associated with the rapid development of the mining and industrial complex of the region.